Odpowiedzi

Najlepsza Odpowiedź!
2010-02-04T20:18:37+01:00
A) √2*25 + √2*4 - √2*16 = 5√2 + 2√2 - 4√2 = 3√2
b) 2√4*5 +3√5*16 - 3√9*5 = 4√5 + 12√5 - 9√5 = 7√5
c) √3*4 - 5√3*9 +4√3*36 = 2√3 -15√3 + 24√3 = 11√3
d) √3*16 + √25*3 - √49*3 = 4√3 + 5√3 - 7√3 = 2√3
20 4 20
2010-02-04T20:19:52+01:00
A]√50+√8-√32=5√2+2√2-4√2=3√2≈3×1,41≈4,23
b]2√20+3√80-3√45=4√5+12√5-9√5=7√5≈7×2,24≈15,68
c]√12-5√27+4√108=2√3-15√3+24√3=11√3≈11×1,73≈19,03
d]√48+5√75-√147=4√3+25√3-7√3=22√3≈22×1,73≈38,06
41 4 41
2010-02-04T20:22:09+01:00
√50 + √8 - √32 = 5√2 + 2√2 - 4√2 = 3√2 = 4,26
2√20 + 3√80 - 3√45 = 4√5 + 12√5 - 9√5 = 7√5 = 15,68
√12 - 5√27 + 4√108 = 2√3 - 15√3 + 24√3 = 11√3 = 19,03
√48 + 5√75 - √147 = 4√3 + 25√3 - 7√3 = 22√3 = 38,06
16 2 16